Regulation of T cells in the tumor microenvironment by histone methylation: LSD1 inhibition—a new direction for enhancing immunotherapy - Xie Xueqing; Peng Yongcan; Lu Wei; Yin Qingling; Ding Jie (Heliyon, 2024)
Although immune checkpoint blockade (ICB) has been shown to achieve durable therapeutic responses in various types of tumors, only 20–40 % of patients benefit from this therapy. A growing body of research suggests that epigenetic modulation of the tumor microenvironment may be a promising direction for enhancing the efficacy of immunotherapy, for example, histone methylation plays an important role in the regulation of T cells in the tumor microenvironment (TME). In particular, histone lysine-specific demethylase 1 (LSD1/KDM1A), as an important histone-modifying enzyme in epigenetics, was found to be an important factor in the regulation of T cells. Therefore, this paper will summarize the effects of histone methylation, especially LSD1, on T cells in the TME to enhance the efficacy of anti-PD-1 immunotherapy. To provide a strong theoretical basis for the strategy of combining LSD1 inhibitors with anti-PD-1/PD-L1 immunotherapy, thus adding new possibilities to improve the survival of tumor patients.